Bridging Clicks and Bricks: How Service Quality Drives Loyalty Through Customer Satisfaction at Uniqlo Indonesia - Proboyo, Adelina; Eugene, Gareth; Tjitra, Jennifer (Review of Management and Entrepreneurship, 2026)
The increasing competition within the fast fashion industry has heightened the importance of customer loyalty, as it directly contributes to a company’s profitability. One way to foster customer loyalty is by delivering high–quality service through both online and offline channels. Previous studies have shown that customer satisfaction can mediate the relationship between offline service quality and customer loyalty. Building on this, the present study incorporates the online service quality to examine whether customer satisfaction mediates the relationship between both online and offline service quality and customer loyalty. This research focuses on customers of Uniqlo Indonesia and the data were collected via online questionnaires distributed through social media platforms, yielding 74 valid responses. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that customer satisfaction fully mediates the relationship between offline service quality and customer loyalty, however, in the case of online service quality, customer satisfaction does not mediate the relationship, suggesting a direct effect between online service quality and customer loyalty.